Treatment of Carbapenem-Resistant Acinetobacter baumannii in Real Life (T-ACI): A Prospective Single-Center Observational Study - Antonio Riccardo Buonomo; Riccardo Scotto; Nunzia Esposito; Giulio Viceconte; Nicola Schiano Moriello; Giulia Zumbo; Ilaria Vecchietti; Amedeo Lanzardo; Carmine Iacovazzo; Francesco Curcio; Emanuela Roscetto; Ivan Gentile (Antibiotics, 2024)
Background: Carbapenem-resistant Acinetobacter baumannii (CRAB) poses significant challenges in healthcare due to its multidrug resistance and high mortality rates among critically ill patients. Results: We enrolled 45 patients. Cefiderocol was administered to 40% of patients, often (38.8%) in combination with other antibiotics. Colistin was administered to 60% of patients and always in combination, mostly with ampicillin–sulbactam. The overall ECS and OCS rates were 77.8% and 66.7%, respectively. Patients treated with an initial cefiderocol-based regimen showed a higher rate of ECS compared with patients initially treated with colistin-based regimens (100% vs. 63%, p < 0.05). Patients treated with cefiderocol alone showed a higher rate of ECS compared with patients treated with cefiderocol-based regimens (100% vs. 70.6%, p < 0.05). No differences in OCS rates were recorded depending on the treatment received. Additionally, cefiderocol regimens were associated with fewer ADRs compared to colistin-based treatment. Methods: This prospective observational study enrolled patients with CRAB infections from January 2022 to August 2023. Patients were treated with cefiderocol-based or colistin-based regimens and were monitored for 28 days to assess early clinical success (ECS), overall clinical success (OCS) and adverse drug reactions (ADRs). Conclusions: This study highlights the potential advantages of cefiderocol, even used as a monotherapy, in treating CRAB, especially when early clinical and laboratory response was assessed. This research contributes to the ongoing discussion on the most effective and safe treatments for combating CRAB infections, supporting the use of cefiderocol in clinical practice.